2006
DOI: 10.1111/j.1365-2958.2006.05326.x
|View full text |Cite
|
Sign up to set email alerts
|

A new ferrous iron‐uptake transporter, EfeU (YcdN), from Escherichia coli

Abstract: SummaryEscherichia coli possesses multiple routes for iron uptake. Here we present EfeU (YcdN), a novel iron acquisition system of E. coli strain Nissle 1917. Laboratory strains of E. coli such as K12 lack a functional (efeU) ycdN gene caused by a frameshift mutation. EfeU, a member of the oxidase-dependent iron transporters (OFeT), is a homologue of the iron permease Ftr1p from yeast. The ycdN gene is part of the ycdNOB tricistronic operon which is expressed in response to iron deprivation in a Fur-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 47 publications
7
139
1
1
Order By: Relevance
“…EfeU is homologous to the yeast high affinity iron permease Frtp1 (17,18). This iron uptake system is defective in E. coli K12 due to a frameshift mutation interrupting the efeU reading frame after amino acid 37 (18). Unlike E. coli K12, many other E. coli strains, such as enterohemorrhagic O157:H7, have an intact efeU sequence and their efeUOB genes expressed in E. coli K12 stimulate iron uptake.…”
Section: The Efeuob Operon Of E Coli O157:h7 Allows Heme Iron Acquismentioning
confidence: 99%
See 1 more Smart Citation
“…EfeU is homologous to the yeast high affinity iron permease Frtp1 (17,18). This iron uptake system is defective in E. coli K12 due to a frameshift mutation interrupting the efeU reading frame after amino acid 37 (18). Unlike E. coli K12, many other E. coli strains, such as enterohemorrhagic O157:H7, have an intact efeU sequence and their efeUOB genes expressed in E. coli K12 stimulate iron uptake.…”
Section: The Efeuob Operon Of E Coli O157:h7 Allows Heme Iron Acquismentioning
confidence: 99%
“…efeB belongs to the iron-regulated efeUOB operon involved in Fe 2ϩ uptake under acidic conditions (17). EfeU is homologous to the yeast high affinity iron permease Frtp1 (17,18). This iron uptake system is defective in E. coli K12 due to a frameshift mutation interrupting the efeU reading frame after amino acid 37 (18).…”
Section: The Efeuob Operon Of E Coli O157:h7 Allows Heme Iron Acquismentioning
confidence: 99%
“…In pathogenic bacteria, uptake pathways may also involve hemolysins, heme-binding proteins, and transferrinbinding proteins (2,11,12). B. subtilis can also use an elemental Fe uptake system YwbLMN (10), which is homologous to Saccharomyces cerevisiae Fet3p/Ftr1p and E. coli EfeUOB systems (13,14). As a result of derepressed transport, fur mutants typically have elevated levels of chelatable iron within their cytosol (15) and are hypersensitive to H 2 O 2 , which reacts with free iron to generate hydroxyl radicals (16).…”
mentioning
confidence: 99%
“…An alternative pathway in E. coli has been described in which iron is removed from surface-bound haemin and imported by the EfeUOB system (Létoffé et al, 2009). The E. coli EfeUOB system was originally described as an acidinduced, low-pH Fe(II) uptake pathway (Cao et al, 2007;Grosse et al, 2006) homologous to the B. subtilis YwbLMN elemental iron uptake system (Ollinger et al, 2006). These elemental iron uptake systems share similarities with the Saccharomyces cerevisiase Ftr1p/Fet3p copper oxidasedependent iron uptake pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Upon binding iron, the Fe-BB complex binds with high affinity to the substrate binding protein FeuA (Miethke et al, 2006), and is transported through the ATP binding cassette (ABC) transport system FeuBC in conjunction with the YusV ATPase (Ollinger et al, 2006). In addition to its own siderophore, B. subtilis pirates other siderophores through expression of specific uptake systems, efficiently utilizes ferric citrate, and has an oxidase-dependent elemental iron transport (OfeT-type) system (Grosse et al, 2006;Ollinger et al, 2006). It has been shown that haemin can rescue the growth of a B. subtilis hemA mutant, which is unable to synthesize haem (Miczák, 1977).…”
Section: Introductionmentioning
confidence: 99%